Long-term efficacy of lipoprotein apheresis and lomitapide in the treatment of homozygous familial hypercholesterolemia (HoFH): a cross-national retrospective survey - Laura D’Erasmo; Antonio Gallo; Angelo Baldassare Cefalù; Alessia Di Costanzo; Samir Saheb; Antonina Giammanco; Maurizio Averna; Alessio Buonaiuto; Gabriella Iannuzzo; Giuliana Fortunato; Arturo Puja; Tiziana Montalcini; et al. (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Homozygous familial hypercholesterolemia (HoFH) is a rare life-threatening condition that represents a therapeutic challenge. The vast majority of HoFH patients fail to achieve LDL-C targets when treated with the standard protocol, which associates maximally tolerated dose of lipid-lowering medications with lipoprotein apheresis (LA). Lomitapide is an emerging therapy in HoFH, but its place in the treatment algorithm is disputed because a comparison of its long-term efficacy versus LA in reducing LDL-C burden is not available. We assessed changes in long-term LDL-C burden and goals achievement in two independent HoFH patients’ cohorts, one treated with lomitapide in Italy (n = 30) and the other with LA in France (n = 29). Results The two cohorts differed significantly for genotype (p = 0.004), baseline lipid profile (p < 0.001), age of treatment initiation (p < 0.001), occurrence of cardiovascular disease (p = 0.003) as well as follow-up duration (p < 0.001). The adjunct of lomitapide to conventional lipid-lowering therapies determined an additional 58.0% reduction of last visit LDL-C levels, compared to 37.1% when LA was added (p adj = 0.004). Yearly on-treatment LDL-C < 70 mg/dl and < 55 mg/dl goals were only achieved in 45.5% and 13.5% of HoFH patients treated with lomitapide. The long-term exposure to LDL-C burden was found to be higher in LA than in Lomitapide cohort (13,236.1 ± 5492.1 vs. 11,656.6 ± 4730.9 mg/dL-year respectively, p adj = 0.002). A trend towards fewer total cardiovascular events was observed in the Lomitapide than in the LA cohort. Conclusions In comparison with LA, lomitapide appears to provide a better control of LDL-C in HoFH. Further studies are needed to confirm this data and establish whether this translates into a reduction of cardiovascular risk.